Management of Acute Hypertensive Emergencies on CKD - Riki Nova; Dessy Abdullah (Science Midwifery, 2022)
Hypertensive emergencies in acute CKD are clinical manifestations of kidney failure which if not treated immediately can result in damage to various internal organs that can be life threatening. One of them is the appearance of symptoms of anasarca edema, which is a serious disease that should not be ignored. Your body experiences swelling, even causing pulmonary edema. Severe anasarca edema can make the body weak and feel uncomfortable. Administration of furosemide iv up to the maximum dose is one of the treatments to avoid damage to other organs.